Dementia Etiologies and Remedies in Traditional Persian Medicine; A Review of Medicinal Plants and Phytochemistry - Shirbeigi, Laila; Dalfardi, Behnam; Abolhassanzadeh, Zohreh; Nejatbakhsh, Fatemeh (Current Drug Metabolism, 2018)
Background: Dementia is a chronic neurodegenerative disease causing progressive and gradual impairment of different brain's cognitive functions. The prevalence of dementia is about 3 to 7% in different parts of the world. Objective: The aim of this study was to determine the etiologies of dementia according to the Traditional Persian Medicine scientists' viewpoint and introduce their recommended herbal remedies for this disease. Method: The authors explored six main Traditional Persian Medicine textbooks for the disease of dementia, its etiologies and related recommended herbal treatments. Two main keywords of “Lisarghes” and “Nesyan” were searched for this purpose. Medical databases, including PubMed, Scopus, Google Scholar, and Science Direct were searched for related articles published between 1966 and 2016 to review the pharmacological components and active ingredients of suggested herbal medicines. Results: According to the Traditional Persian Medicine, dementia is resulted from brain dystemperament, a condition caused by cold and moist or cold and dry tempers. To treat this disease, Traditional Persian scientists recommended various herbal remedies. Current studies have demonstrated that some of these medicinal plants have beneficial effects for the aforementioned disease, including acetyl cholinesterase inhibitory function, neuroprotective effects, and memory enhancing role. Conclusion: The Traditional Persian Medicine literature suggested different herbal remedies for treating dementia. Modern studies support the usefulness of some of these medicines. However, the effect of a large number of these remedies has remained unexamined, a matter which needs to be investigated in future researches.
Keywords: neuropsychiatry